2022
DOI: 10.1039/d1ta10681c
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-walled carbon nanotube-coupled CoNi MOF composite enhances the oxygen evolution reaction through synergistic effects

Abstract: Optimizing the composition, structure, and carrier of non-noble-metals-based MOFs material effectively improve their electrocatalytic performances. Recently, CoNi bimetallic MOFs have attracted noticeable notes for hydrogen production by alkaline water electrolysis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Recently, a new class of inorganic–organic crystalline hybrid materials, namely, metal–organic frameworks (MOFs), have been found, which form periodic network structures through self-assembly of metal nodes (metal ions or metal clusters) and organic ligands. MOF materials have attracted extensive attention in the field of electrocatalysis due to their high specific surface area, tunable pore size, diversity of central metals, organic ligands, and easy structure tunability . Among them, zeolitic imidazolate frameworks (ZIFs) have become a well-known family of MOFs due to their zeolite-like structure, demonstrating broad application potential in energy storage, adsorption, catalysis, gas separation, supercapacitors, batteries, and electrochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new class of inorganic–organic crystalline hybrid materials, namely, metal–organic frameworks (MOFs), have been found, which form periodic network structures through self-assembly of metal nodes (metal ions or metal clusters) and organic ligands. MOF materials have attracted extensive attention in the field of electrocatalysis due to their high specific surface area, tunable pore size, diversity of central metals, organic ligands, and easy structure tunability . Among them, zeolitic imidazolate frameworks (ZIFs) have become a well-known family of MOFs due to their zeolite-like structure, demonstrating broad application potential in energy storage, adsorption, catalysis, gas separation, supercapacitors, batteries, and electrochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
“…MOF materials have attracted extensive attention in the field of electrocatalysis due to their high specific surface area, tunable pore size, diversity of central metals, organic ligands, and easy structure tunability. 16 Among them, zeolitic imidazolate frameworks (ZIFs) have become a well-known family of MOFs due to their zeolite-like structure, demonstrating broad application potential in energy storage, 17 adsorption, 18 catalysis, 19 gas separation, 20 supercapacitors, 21 batteries, 22 and electrochemical sensors. 23 However, the poor electrical conductivity of most MOFs restricts the transfer paths of electrons, which also limits the electron transfer paths on the electrode surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Binding energy is negatively related to surface electron density, 28 this means that the anatase and rutile TiO 2 in TiO 2 -TELMs were closely connected due to the formation of homojunction structures, and the electron density gradually increases with increasing the ratio of rutile TiO 2 . 29–31 When the ratio of rutile TiO 2 exceeds to a certain value, for example 65% in this work, the electron density of TiO 2 in the TiO 2 -TELM sample gradually decreases, and the electrons transfer from rutile to anatase TiO 2 . Therefore, this suggests that the electron transfer from anatase to rutile or from rutile to anatase should be adjusted by the ratio of rutile or anatase in TiO 2 -TELMs.…”
Section: Resultsmentioning
confidence: 62%
“…After further solvothermal treatment, the flower‐shaped composite transformed into a spherical structure (Figure 2c) and then converted to a spherical V‐doped Ni‐MOF on NiV‐OH surface upon the addition of the DHTA. Furthermore, the three‐dimensional open spherical framework can provide increased active area and improve mass transfer [8b,16] . Transmission electron microscopy (TEM) images of the ultrasonically exfoliated catalyst fragments showed that the V 0.09 −Ni 0.91 MOF surface was flake‐like (Figure 2d), and some nanoparticles with an average size of about 0.89 nm (inset 2e) were uniformly distributed on its surface (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%